Mengenali Dan Tata Laksana Agitasi Pada Skizofrenia Di Instalasi Gawat Darurat Rumah Sakit - Rina Amtarina (Fakultas Kedokteran Universitas Riau, 2023)
Agitation is common condition that can be found in psychotic disorder such as schizophrenia. Agitation is marked by restlessness, excessive motoric and verbal. This condition caused the patient brought to emergency because the crucial condition. It is challenging for medical staff to make an accurate diagnosis and manage the agitated patient. Agitation can go up into aggressive behavior and endangering everyone. In this literature review, we will discuss treatment to reduce agitation in schizophrenic patients.